GEOLOGIC AND PETROGRAPHIC ASPECTS FOR COAL EXPLORATION IN SANGATTA-EAST KALIMANTAN - BINARKO SANTOSO; BUKIN DAULAY (Puslitbang tekMIRA, 2009)
The Miocene Sangatta coals indicate similarities and differences in type and rank characteristics. The phenomena express the geological setting that includes the stratigraphic aspect and the pres- ence of intrusive body. The stratigraphic aspect relates to geologic age and cover thickness; the lower coal seam having a thicker cover has a higher rank than the upper coal seam. The intrusive body changes the rank of the coal up to semi-anthracite. The coals that are not affected by the intrusion have rank of brown coal to subbituminous. The rank of the coals increases from east to west toward the Meratus Range due to the cover thickness, where the western part has a thicker cover than the eastern part. These geological phenomena could be an exploratory target for the prospective coals.